Single-nitrogen atom incorporation into B=B bond via the N=N bond splitting of diazo compound and diazirine - Zhu, Lizhao (2023)
Triboraazabutenyne 3 is synthesized by the reaction of diboraazabutenyne 1 with aryl boron dibromide followed by the reduction. The ligand exchange to replace phosphine on the terminal sp2 B atom with carbene furnishes 4. 11 B NMR, solid-state structures, and computational studies disclose that 3 and 4 feature the extremely polarized B=B bond. 4 readily splits the N=N bond of both diazo compound and diazirine under ambient conditions, whereby one nitrogen atom is incorporated into the B=B moiety leading to a neutral diboraazaallene 6. The mechanism of the reaction between 4 and diazo compound is extensively investigated by density functional theory (DFT) calculations, as well as the isolation of an intermediate.